Kontribusi, Tantangan, dan Strategi Penyelesaian Pembiayaan Bermasalah pada Obligasi Syariah Sukuk di Pasar Modal Syariah: Contributions, Challenges, and Strategies for Resolving Problem Financing in Sukuk Islamic Bonds in the Islamic Capital Market - Ardiansyah, Ahmad Laskar Putra; Ainna Ningrul; Sulistyowati, Sulistyowati (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
This research analyzes the contributions, challenges, and strategies for resolving problematic financing in Sharia bonds (sukuk) within the Islamic capital market. Sharia bonds serve as a vital financial instrument for economic development, providing additional funding for corporate growth and attracting investors. Through a systematic literature review, this study explores the foundational principles and legal regulations governing sukuk, including Law No. 10 of 1998 and fatwas issued by the Indonesian Ulama Council's National Sharia Board (DSN MUI). Findings reveal that sukuk positively impact economic development by promoting monetary movement and fostering corporate expansion. However, risks such as default, restructuring, and non-payment emerge due to weak credit feasibility analysis, poor corporate governance, and volatile economic conditions. These risks are exacerbated by insufficient investor education and a lack of robust regulatory enforcement. To address these issues, the study proposes strengthening credit analysis procedures, enhancing corporate governance practices, improving investor literacy, and developing transparent financial instruments.